The Impact of Social Interaction, Academic Achievement, and Cognitive Flexibility Levels on Clinical Reasoning: Statistical Discourse Analysis - Cetin Toraman; Canan Akman; Aysen Melek Aytug-Kosan; Gunes Korkmaz (Journal of Education in Science, Environment and Health)
This study aims to analyze the impact of intern physicians' social interaction during teamwork, their cognitive flexibility and academic achievement on clinical reasoning. The study, designed through sequential exploratory mixed method, was carried out with 20 intern physicians working in 4 teams. The process of how they approach to the case was recorded. The verbal interactions made during the discussions in the teams were analyzed, the discourses obtained from the videos were coded and modelled by regression. In addition, the cognitive flexibility and academic achievement levels of intern physicians were also included in the regression modelling. The results showed that, according to the initial signs and symptoms of the first period of the case (when uncertainty was high), the team members informing each other resulted in success in clinical reasoning. Although guiding in the first period was not very effective, excessive guiding in the second period played a negative role in clinical reasoning. In the second period, ignoring, reminding, and suggesting had a negative impact on clinical reasoning. Our study demonstrated that academic achievement and cognitive flexibility levels of the students in teamwork has a positive impact on the quality of clinical reasoning. Moreover, for effective clinical reasoning, the quality of discourses in the team is more important than how many discourses are created during the discussions